Pengaruh Brand Awareness dan Electronic Word of Mouth (e-WOM) terhadap Keputusan Pembelian Konsumen Produk Fore Coffee Di Bekasi: The Influence of Brand Awareness and Electronic Word of Mouth (e-WOM) on Consumer Purchase Decisions of Fore Coffee Products in Bekasi - Nurul Fajriningtias; Desy Suryani; Martinus Wahyu Purnomo (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
The increasingly competitive coffee shop industry in Bekasi has encouraged businesses to implement effective marketing strategies to influence consumers' purchase decisions. This study aims to analyze the effect of brand awareness and electronic word of mouth (e-WOM) on the purchase decisions of product Fore consumers in Bekasi, both partially and simultaneously. This study employed a quantitative approach using primary data collected through questionnaires distributed to 96 Fore Coffee consumers in Bekasi, with the sample size determined using the Lemeshow formula. The data were analyzed using multiple linear regression, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination. The results indicate that brand awareness and electronic word of mouth (e-WOM) have a positive and significant effect on purchase decisions, both partially and simultaneously. Simultaneously, both variables explain 66.3% of the variance in purchase decisions, while the remaining 33.7% is influenced by other factors outside the scope of this study. These findings suggest that strengthening brand awareness and effectively managing electronic word of mouth (e-WOM) can serve as effective marketing strategies to enhance consumers' purchase decisions at Fore Coffee in Bekasi.